Richard III - Shakespeare, William, 1564-1616 (Yale University Press, 2008)
Treacherous, power-hungry, untempered by moral restraint, and embittered by physical deformity, Richard, the younger brother of King Edward IV, is ablaze with ambition to take England's throne. Richard III, Shakespeare's long chronicle of Richard's machin.
Keywords: Richard -- III, -- King of England, -- 1452-1485 -- Drama.; Richard -- III, -- King of England, -- 1452-1485; Great Britain -- History -- Richard III, 1483-1485 -- Drama.; LITERARY CRITICISM -- Shakespeare.; DRAMA -- Shakespeare.; DRAMA -- General.; Great Britain; English Literature.; English.; Languages & Literatures.; 1483-1485; Drama; History